585. Safety and Immunogenicity of SARS-CoV-2 Vaccination in Children with a History of MIS-C. (15th December 2022) - Howe, Harrison L; Amarin, Justin Z; Hayek, Haya; Talj, Rana; Spieker, Andrew J; Katz, Sophie E; Patrick, Anna E; Parra, David; Fernandez, Kailee; Eason, Joan E; Rankin, Danielle A; Rankin, Danielle A; et al.
Abstract: Background: Multisystem Inflammatory Syndrome in Children (MIS-C) is a rare sequela that typically develops 2–6 weeks after SARS-CoV-2 infection. According to CDC recommendations, children who recover from MIS-C should be vaccinated 90 days after diagnosis, but safety and immunogenicity data are lacking. Our aim was to evaluate the safety and immunogenicity of one dose of the BNT162b2 vaccine in children with a history of MIS-C. Methods: We conducted a longitudinal study of children with MIS-C admitted to Monroe Carell Jr. Children's Hospital at Vanderbilt from 7/11/2020 to 3/23/2022. Children were eligible if they met CDC's MIS-C criteria and had blood collected before and after SARS-CoV-2 vaccination. Clinical data were obtained from medical records and injection site and systemic reactions were recorded for a week following SARS-CoV-2 vaccination via memory aids. IgG against SARS-CoV-2 nucleocapsid (N), spike receptor-binding domain (RBD), and spike extracellular domain (ECD) was detected using an enzyme-linked immunosorbent assay. The first anti-RBD and anti-ECD levels prevaccination and postvaccination were compared using the paired-samples t -test. Results: Seven children were included, of whom five were male and five were non-Hispanic White. The first blood sample was collected 3–44 days following admission. The median age at admission was 15.8 years (IQR, 10.5–14.7 years), and the median time from admission to vaccination was 7 months (IQR, 6–8 months). Five children each had injection site or systemic reactions (Figure 1 ); the majority were mild or moderate and occurred within 2 days of vaccination. Children were followed for a median of 5.6 months (4.3–6.2 months) postvaccination; none developed MIS-C recurrence. Following vaccination, mean anti-RBD and anti-ECD levels increased by 2.0 (1.2–2.9; p < 0.001) and 1.9 (1.2–2.6; p < 0.001) absorbance units, respectively (Figure 2 ). A sensitivity analysis excluding children with antibody evidence of reinfection (increase in anti-N level ≥ 0.5) showed similar results. Figure 1 Safety of SARS-CoV-2 vaccination in children with a history of MIS-C. Figure 2 Immunogenicity of SARS-CoV-2 vaccination in children with a history of MIS-C. The best-fit lines (LOESS) are indicated in black. The dashed line indicates the day of vaccination. Conclusion: SARS-CoV-2 vaccination is safe and immunogenic in children with a history of MIS-C, with no documented recurrence of MIS-C–like illness. Further studies are needed to determine the optimal timing, safety, and immunogenicity of vaccination following MIS-C. Disclosures: Natasha B. Halasa, MD, Quidel: Grant/Research Support|Quidel: equipment donation|Sanofi: Grant/Research Support|Sanofi: HAI testing and vaccine donation.